De verzameling - Hoet, Jan (Gent : Ludion, 1999)
't Jolle, Sven ; Van den Abbeel, Jan ; Abramovic, Marina ; Accardi, Carla ; Acconci, Vito ; Adami, Valerio ; Alechinsky, Pierre ; van Amen, Woody ; Van Anderlecht, Englebert ; Andre, Carl ; Rossi Andrea, Andrea ; Anselmo, Giovanni ; Appel, Karel ; Appelt, Dieter ; Apple, Billy ; Arman ; Art & Language ; Artschwager, Richard ; Assig, Martin ; Bacon, Francis ; Bade, David ; Baikas, Nicos ; Baj, Enrico ; Bar-El, Ido ; Barbaix, René ; Barry, Robert ; Bassiri, Bizhan ; Becher, Bernd & Hilla ; Beecroft, Vanessa ; Bejar, Raphaël ; Bekaert, Piet ; Bergen, Emiel ; van Bergen, Thé ; Berghe, Roland Van Den ; Berti, Simone ; Bertrand, Gaston ; Bervoets, Fred ; Beullens, André ; Beuys, Joseph ; Beyls, Peter ; Biberstein, Michael ; Bijl, Guillaume ; Birnbaum, Dara ; Blaussyld, Maurice ; Boetti, Alighiero ; Bogaert, André ; Bogaerts, Gaston ; Bogart, Bram ; van Bohemen, Kees ; Boltanski, Christian ; Bonnet, Anne ; Boon, Elke ; Borden, William R. ; Bourke, Brendan ; Bowen, Paul ; De Brabandere, Mario ; Braeckman, Dirk ; Brey, Ricardo ; van den Broeck, Frank ; Broodthaers, Marcel ; Brouwn, Stanley ; Bruch, Klaus vom ; De Bruyckere, Berlinde ; Buren, Daniel ; Burkhart, Kathe ; Burki, Marie José ; Burssens, Jan ; Bustamante, Jean-Marc ; Buthe, Michael ; Cabrita Reis, Pedro ; Cai Guo-Qiang ; Calzolari, Pierpaolo ; Cane, Louis ; Caniaris, Vlassis ; Carlier, Jan ; Carmi, Eugenio ; Ceccobelli, Bruno ; Charlier, Jacques ; Charoux, Jac (Jacques) ; Chlanda, Marek ; Christo ; Cingolani, Marco ; Claus, Hugo ; Clement, Frans ; De Clerck, Antoon ; de Clercq, Hugo ; De Clercq, Maurice ; Close, Chuck ; Cobbaert, Jan ; Cole, Willem ; Coleman, James ; Coolens, Bert (Berten, Robert) ; Copers, Leo ; de Cordier, Thierry ; Corillon, Patrick ; Corneille ; Cortier, Amédée ; etc.
De Opening (SMAK), SMAK (Stedelijk Museum voor Actuele Kunst) Gent, 1999-05-09. 1999-12-05
boek